Exploring Multi-Scale Thermal Behaviour in Pin-on-Disc Systems for Organic, Metallic, Ceramic, and Polymer Composites - Hemant Nagoriya; Gaurav Arora (Mechanics of Advanced Composite Structures)
This paper presents a multi-scale strategy for the thermal simulation of frictional systems, such as brakes, considering the microscale properties of the polymer composites. A finite element model is supposed to model the system components at the macro scale. At the microscale, the thermal properties are evaluated to identify the effective thermal properties of the polymer composites. As regards wear, Archard's law is used with a wear rate coefficient depending on temperature. The micro-scale properties of the polymer composites are integrated into the macro-scale model using the COMSOL computational package. In the conducted study, it is determined that the contact temperature for organic disk brake pad material reaches the highest value at 727 K, followed by ceramic material pad at 691 K, and semi-metallic material at 689 K. Focusing on epoxy and epoxy-fiber composites, it is observed that the Kevlar-epoxy composite exhibits temperature performance characteristics comparable to those of the semi-metallic and ceramic materials, registering a contact temperature of 693 K. In contrast, both epoxy and epoxy-carbon fiber composites display significantly higher temperatures, with values of 1254 K and 944 K, respectively. Consequently, these findings suggest that Kevlar epoxy shows promise in serving as a future brake pad material for the automotive industry. The multi-scale study on different materials focusing on the use of computational results for replacing the traditional brake pad material with advanced composites is the novelty of the study.